PENGARUH HARGA DAN PROMOSI TERHADAP KEPUASAN KONSUMEN SERTA DAMPAKNYA PADA LOYALITAS KONSUMEN PT.CAMPINA ES KRIM INDUSTRI (KANTOR PERWAKILAN CAKUNG) - Wahyu Murti; Fikri Septiadi (Fakultas Ekonomi Universitas Borobudur, 2018)
This study aims to determine the extent of the effect of prices and promotions on customer satisfaction and its impact on consumer loyalty to PT. Capina Es Krim Industri (Cakung Representative Office)The data used in this study is primary data collected from respondents' answers based on the questionnaire given, which is as many as 84 people. Data processing method uses path analysis method (path analysis) with the help of SPSS version 23.0 Testing statistics using individual parameter Significance Test (t Test) and Simultaneous Significance Test (Test f).The results of the study show that simultaneously the price, promotion and customer satisfaction variables have a significant effect on consumer loyalty. Keywords: Price, Promotion, Consumer Satisfaction, Consumer Loyalty